Examining the effectiveness of psychological interventions for marginalised and disadvantaged women and individuals who have experienced gender-based violence: protocol for a scoping review. Issue 7 (7th July 2022) - Yalcinoz-Ucan, Busra; Zilney, Laura; Zientarska-Kayko, Agnes; Ireland, Timothy; Browne, Dillon Thomas
Abstract : Introduction: Exposure to gender-based violence (GBV) has devastating psychological outcomes for victims/survivors. Particularly in conditions where GBV intersects with multiple forms of oppression, the negative impacts of violence are more challenging to overcome and potential pathways for recovery become less accessible. However, evidence regarding the availability and effectiveness of mental health interventions for GBV survivors from marginalised and disadvantaged communities has yet to be systematically integrated and synthesised. The proposed scoping review will examine the relevant literature regarding the availability and effectiveness of psychological interventions for survivors of GBV from marginalised and disadvantaged backgrounds. This review will (i) document what psychological interventions have been available and empirically established for marginalised and disadvantaged women and individuals with experiences of GBV, (ii) provide a narrative examination of the treatment outcomes of identified interventions regarding their effectiveness and (iii) examine the degree to which GBV interventions in selected sources are designed and applied with a recognition of the social determinants of mental health. Methods and analysis: The search for the proposed scoping review will include five electronic databases: PsycINFO, Scopus, Web of Science, Ovid Medline, and CINAHL. The database search will be completed in June 2022. An additional search will be conducted before the completion of the study in December 2022. The search will target research studies published after 2010. The primary eligibility criterion for study selection is having a focus on psychological interventions for GBV survivors from marginalised and disadvantaged groups. Two reviewers will conduct screening and data extraction. The data will be evaluated to map the treatment outcomes of interventions and their effectiveness. Implications for clinical services will be discussed. Ethics and dissemination: No ethical consideration is foreseen for this scoping review. The dissemination will be done through a publication in a top-tier open access journal and conference presentations.